Church acoustics and the influence of occupancy - Victor Desarnaulds (2002)
Speech intelligibility is usually evaluated, by the use of objective parameters, in unoccupied rooms due to practical considerations. However, under normal conditions, the room occupancy can increase or decrease the values of speech intelligibility by the effect of the additional sound absorption present in the room or by the change in S/N ratio. Measurements were carried out in six churches with and without occupancy. The results show that occupancy induces a mean increase for the speech intelligibility of STI (STIoccupSTIunoccup) of 0.050 with the use of a public address system (PA) and 0.035 without a PA. This increase is caused mainly by the reduction of the room reverberation time, due to the increased sound absorption and by the reduction of the additional RT induced by the PA (using loudspeakers with strong directivity oriented towards the congregation area). The variations in the speech intelligibility values with occupancy can be predicted in churches by employing new empirical formulations. The decrease in S/N ratio (due to the background sound level augmentation by the presence of people and by sound level decrease with distance in the congregation area), or the poor directivity and orientation of the sound sources, could reduce the speech intelligibility gain in particular cases. Other effects induced by the congregation, such as the variations of humidity and temperature, generally have negligible effect on speech intelligibility.